Therapeutic strategy of biological macromolecules based natural bioactive compounds of diabetes mellitus and future perspectives: A systematic review - Naiyer Shahzad; Abdullah R. Alzahrani; Ibrahim Abdel Aziz Ibrahim; Imran Shahid; Ibrahim M. Alanazi; Alaa Hisham Falemban; Mohammad Tarique Imam; Nehal Mohsin; Mohd Fahami Nur Azlina; Palanisamy Arulselvan (Heliyon, 2024)
High blood glucose levels are a hallmark of the metabolic syndrome known as diabetes mellitus. More than 600 million people will have diabetes by 2045 as the global prevalence of the disease continues to rise. Contemporary antidiabetic drugs reduce hyperglycemia and its consequences. However, these drugs come with undesirable side effects, so it's encouraging that research into plant extracts and bioactive substances with antidiabetic characteristics is on the rise. Natural remedies are preferable to conventional anti-diabetic drugs since they are safer for the body, more affordable and have fewer potential adverse effects. Biological macromolecules such as liposomes, niosomes, polymeric nanoparticles, solid lipid nanoparticles, nanoemulsions and metallic nanoparticles are explored in this review. Current drug restrictions have been addressed, and the effectiveness of plant-based antidiabetic therapies has enhanced the merits of these methods. Plant extracts' loading capacity and the carriers' stability are the primary obstacles in developing plant-based nanocarriers. Hydrophilic, hydrophobic, and amphiphilic drugs are covered, and a brief overview of the amphipathic features of liposomes, phospholipids, and lipid nanocarriers is provided. Metallic nanoparticles' benefits and attendant risks are highlighted to emphasize their efficiency in treating hyperglycemia. Researchers interested in the potential of nanoparticles loaded with plant extracts as antidiabetic therapeutics may find the current helpful review.